Effects of prolonging the interval from progestin removal to prostaglandin F2α injection from 16 to 17 d in a long-term estrus synchronization protocol in beef heifers1. Issue 2 (7th April 2021) - Oosthuizen, Nicola; Melo, Gabriela D; Seidel, George E; Stewart, R Lawton; Rowden, Larry; Lamb, Graham C; Fontes, Pedro L P
Abstract: To determine effects of delaying the injection of prostaglandin F2α (PGF) and fixed-time artificial insemination (TAI) in the 14-d CIDR-PG protocol, 1, 049 Angus heifers at six locations were enrolled in a completely randomized design. Within location heifers were randomly assigned to one of two treatment groups: 1) PG16 ( n = 518), heifers received a controlled internal drug release (CIDR) insert on d 0 for 14 d, a 25-mg injection of PGF 16 d after CIDR removal (d 30), and a 100-µg injection of gonadotropin-releasing hormone concurrent with TAI 66 ± 2 h later; or 2) PG17 ( n = 531), heifers were treated the same as PG16, however, PGF was administered 17 d after CIDR removal (d 31), and heifers were TAI 66 ± 2 h later. Estrus detection patches were applied to a subset ( n = 482) of heifers at the time of PGF administration and were examined for activation at TAI. Dominant follicle diameter was determined via transrectal ultrasonography at PGF administration and TAI in a subset of heifers ( n = 116). Transrectal ultrasonography was performed to determine pregnancy rates to TAI (PR/AI) between 30 and 45 d after TAI. Estrus expression prior to TAI differed by treatment where PG17 heifers had greater ( P < 0.01) expression of estrus than PG16 heifers (57.8 ± 6.1% vs. 43.4 ± 6.1%, respectively). Nevertheless, dominant follicle diameters at PGF and at TAI were similar ( P ≥ 0.59) between PG16 and PG17 heifers. In addition, PR/AI did not differ ( P = 0.29) between PG16 and PG17 treatments (50.5 ± 3.2% vs. 45.7 ± 3.1%, respectively). Results of this experiment indicate that delaying the injection of PGF and TAI in the 14-d CIDR-PG protocol increased estrus expression prior to TAI yet did not improve fertility in beef heifers.